2007
DOI: 10.1063/1.2828111
|View full text |Cite
|
Sign up to set email alerts
|

Full-field imaging of nonclassical acoustic nonlinearity

Abstract: The feasibility of full field shearographic detection of nonclassical acoustic nonlinearity is investigated. Traditional frequency analysis of the sinusoidally excited sample, as used in scanning techniques, turns out to be not practical due to the inherent optical detection nonlinearity of the shearography system itself. An alternative method, based on determining the asymmetry between shearographic images stroboscopically obtained for positive and negative displacements, is proposed. This approach allows us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…fig. 15 depicts the experimental excitation amplitude dependence of the asymmetry-averaged image obtained on the test sample as was outlined in previous work [13]. the underlying resulting dynamic fringe pattern depends not only on the vibration pattern, but also on the shearing distance and on the nonlinear interferometric transfer function, making it quite hard to predict or interpret the obtained intensity-averaged images and their dependence on the vibration amplitude.…”
Section: Nonlinear Generation Of Harmonic and Non-mentioning
confidence: 98%
See 3 more Smart Citations
“…fig. 15 depicts the experimental excitation amplitude dependence of the asymmetry-averaged image obtained on the test sample as was outlined in previous work [13]. the underlying resulting dynamic fringe pattern depends not only on the vibration pattern, but also on the shearing distance and on the nonlinear interferometric transfer function, making it quite hard to predict or interpret the obtained intensity-averaged images and their dependence on the vibration amplitude.…”
Section: Nonlinear Generation Of Harmonic and Non-mentioning
confidence: 98%
“…substantial work on nonlinearity in adhesive joints was performed by Hirsekorn [8], [9], Zaitsev and Gusev et al [10], and Van den abeele, johnson et al [11], [12] obtained very interesting experimental and theoretical results related to acoustical nonlinearity in bulk materials. recently, the authors have shown that a similar approach can be used in combination with dynamic shearographic imaging providing full-field visualization of the defect-selective acoustic nonlinearity [13]. the advantage of this approach is the combination of an increased detection speed with nonlinearly enhanced defect contrast.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…They have attracted much attention, by virtue of their non-contact, non-destructive nature and high flexibility of implementation. [1][2][3][4][5][6] Moreover, possible bandwidth limitations of electronic detection can be circumvented by making use of an optical delay line. 7,8 Optical detection of SAW induced displacements at a single location can be done with high sensitivity, e.g., by interferometric detection, 9,10 laser beam deflection, 11,12 modulated optical reflection, 13 or heterodyne diffraction detection.…”
Section: Introductionmentioning
confidence: 99%